Biochemical, Immunological, and Histopathological Assessment of Carbon Tetrachloride (CCl₄)-Induced Hepato-Renal Toxicity in Rats - Mervat Kamel Kadhom (Indonesian Journal on Health Science and Medicine, 2025)
General Background Carbon tetrachloride (CCl₄) is a well-established experimental toxicant known to induce liver and kidney injury through oxidative and inflammatory mechanisms. Specific Background CCl₄ metabolism generates reactive free radicals that disrupt biochemical homeostasis, provoke immune imbalance, and produce characteristic histopathological damage in hepatic and renal tissues. Knowledge Gap Despite extensive use of CCl₄ models, integrated evaluation combining biochemical, immunological, and histopathological parameters remains limited. Aims This study aimed to assess dose-dependent hepato-renal toxicity of CCl₄ in rats using biochemical markers, cytokine profiling, and tissue histology. Results CCl₄ exposure increased serum AST, ALT, urea, creatinine, cholesterol, and triglycerides, elevated TNF-α and IL-6, reduced IL-10, and induced marked hepatic and renal histopathological alterations. Novelty The study provides a consolidated multi-system assessment highlighting immune dysregulation alongside biochemical and structural injury. Implications These findings underscore the importance of combined biochemical, immunological, and histopathological approaches for mechanistic evaluation of chemical-induced hepato-renal toxicity.Keywords : Carbon Tetrachloride Toxicity, Hepatorenal Injury, Oxidative Stress, Proinflammatory Cytokines, Histopathological AlterationsHighlight : Dose-dependent enzyme, lipid, urea, and creatinine elevations indicate progressive liver and kidney dysfunction. Pro-inflammatory mediators increased while anti-inflammatory response declined, demonstrating marked immune imbalance. Tissue examinations revealed cellular degeneration, inflammatory infiltration, fibrosis, and tubular damage severity increased with dose.